A High-Performance Process for the Production of Non-Woven, Spunlace Fibres, Based on Mixtures of Viscose and Polyester Fibres. Part 1 - Methodology, Scope and the Expected Results of the Studies - Michał SĄSIADEK; Waldemar WOŹNIAK; Maciej NIEDZIELA (Communications of International Proceedings, 2021)
This article presents a research process concerning the selection of optimal parameters for the carding process in the high-performance production of Spunlace fibres. The individual components of the technological line have been characterised and are described with special attention to the carding module. The reference product, that is, the fibre, based on a mixture of polyester - 80% and viscose - 20% and the methodology and scope of the planned tests, have been presented. The results of the study are presented and discussed in the second part of the article.
Keywords: Spunlace fibre; fibre carding process; mechanical fibre strength both longitudinally and transversely.